Influence of recycled slag aggregates on the conductivity and strain sensing capacity of carbon fiber reinforced cement mortars. (30th September 2018) - Baeza, F.J.; Galao, O.; Vegas, I.J.; Cano, M.; Garcés, P.
Highlights: Cement mortars with Electric Arc Furnace slag aggregates show higher strengths. Recycled EAF slag aggregates enhance the conductivity of CF reinforced mortars. Percolation was achieved with lower CF dosage for EAF slag aggregate mortars. CF reinforced mortars with EAF slag aggregates presented strain sensing capacity. The highest sensitivity was measured for EAF slag mortars with 1.9 vol% CF. Abstract: The electrical resistivity of carbon fiber reinforced cement composites (CFRCC) has been widely studied for the functional applications of these composites. CFRCC with enhanced electrical properties can be used as strain or damage sensor, heating or deicing material, or anode in different electrochemical techniques, like chloride extraction or cathodic protection. In this work, carbon fiber reinforced cement mortars have been prepared using a conductive aggregate produced from the valorization of Electric Arc Furnace slag (EAF slag). Cement based mortars containing EAF slag aggregates revealed lower resistivity; hence, the carbon fiber percolation threshold decreased. Additionally, the strain sensing capacity of those composites with conductive aggregates was also enhanced, indicating similar sensitivity and lower dispersion than equivalent mortars containing limestone aggregates. The best linear regressions between the electrical and mechanical measures were achieved for EAF slag cement mortar containing 1.29 vol% of oxidized carbon fibers.